Flood Susceptibility Assessment in Arid Areas: A Case Study of Qatar - Mohammad Zaher Serdar (17191381) (2022)
Over the past decade, the adverse impacts of climate change and excessive urbanization have contributed to several unfamiliar and costly floods in the Gulf Cooperation Council (GCC), especially in Qatar. With limited historical rainfall records and unprecedented precipitation intensities impacting the efficiency of hydrological models, the multi-criteria decision analysis (MCDA) presents a suitable alternative approach to assess and identify flood-susceptible areas. In this study, we applied MCDA to several factors that contribute to flood susceptibility, namely: elevation, slope, groundwater depth, distance to a drainage system, and land use. These criteria were assigned different weights based on their contribution and previous literature and later underwent a sensitivity analysis. The study’s results correlate well with recent flooding events, proving the method’s efficiency in identifying hotspots. This study is expected to provide a rapid tool to support the decision-making process for future urban expansion, sustainable development, and resilience planning in Qatar. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su14159792